Shared services as a new organizational form - Bondarouk, Tanya, 1967- (Advanced series in management (Unnumbered), 2014)
Organizations increasingly establish Shared Service Centers, either for transactional (administrative) or transformational (organizational change) purposes. Their popularity originates from a combination of efficiency gains and an increase in service quality, without giving up control of the organizational and technical arrangements. The belief is that shared services should maximize the advantages of centralized and decentralized delivery of business functions. The volume deals with sample questions, including: What do shared service models involve? What are the structural arrangements between shared services and the organizations? Which business processes can and/or should be shared? What are the structural differences between shared services in different business processes? This ASM volume intends to move towards more systematic research action. Five main theoretical priorities shape the content of the volume: conceptualizing shared services for different types of business processes, business strategy and shared services, shared services and performance, pluralism in organizing shared services, and governance of shared services in different types of organizations.